Mandibular Non-Hodgkin Lymphoma. Case Presentation and Literature Review - Guevara Cabrera, Osmani (2025)
Non-Hydroxychondroma is a heterogeneous group of malignancies with lymphoreticular histogenesis. Most cases begin in the lymph nodes, although they also occur in extranodal forms. In the oral cavity, lymphomas can affect the jaws or soft tissues as the primary manifestation. We present a case of mandibular lymphoma with the aim of studying its clinical features, radiographic appearance, and histology.